New insights into the biomechanics of Legg-Calvé-Perthes' disease: The Role of Epiphyseal Skeletal Immaturity in Vascular Obstruction. Issue 2 (February 2018) - Pinheiro, M.; Dobson, C. A.; Perry, D.; Fagan, M. J.
Abstract : Objectives: Legg–Calvé–Perthes' disease (LCP) is an idiopathic osteonecrosis of the femoral head that is most common in children between four and eight years old. The factors that lead to the onset of LCP are still unclear; however, it is believed that interruption of the blood supply to the developing epiphysis is an important factor in the development of the condition. Methods: Finite element analysis modelling of the blood supply to the juvenile epiphysis was investigated to understand under which circumstances the blood vessels supplying the femoral epiphysis could become obstructed. The identification of these conditions is likely to be important in understanding the biomechanics of LCP. Results: The results support the hypothesis that vascular obstruction to the epiphysis may arise when there is delayed ossification and when articular cartilage has reduced stiffness under compression. Conclusion: The findings support the theory of vascular occlusion as being important in the pathophysiology of Perthes disease. Cite this article : M. Pinheiro, C. A. Dobson, D. Perry, M. J. Fagan. New insights into the biomechanics of Legg-Calvé-Perthes' disease: The Role of Epiphyseal Skeletal Immaturity in Vascular Obstruction. Bone Joint Res 2018;7:148–156. DOI: 10.1302/2046-3758.72.BJR-2017-0191.R1.